A cell culture platform for Cryptosporidium that enables long-term cultivation and new tools for the systematic investigation of its biology. Issue 3 (March 2018) - Miller, Christopher N.; Jossé, Lyne; Brown, Ian; Blakeman, Ben; Povey, Jane; Yiangou, Lyto; Price, Mark; Cinatl, Jindrich; Xue, Wei-Feng; Michaelis, Martin; Tsaousis, Anastasios D.
Graphical abstract: Highlights: We have developed a cultivation system for Cryptosporidium that enables long-term culturing. Lipidomics fingerprinting was used to demonstrate the identity of the oocysts. Atomic force microscopy imaging was performed for thin- and thick-walled Cryptosporidium oocysts. The cell culturing is easy to handle and enables propagation and cryopreservation. The new tools can be used for a detailed investigation of Cryptosporidium 's biology. Abstract: Cryptosporidium parasites are a major cause of diarrhoea that pose a particular threat to children in developing areas and immunocompromised individuals. Curative therapies and vaccines are lacking, mainly due to lack of a long-term culturing system of this parasite. Here, we show that COLO-680N cells infected with two different Cryptosporidium parvum strains produce sufficient infectious oocysts to infect subsequent cultures, showing a substantial fold increase in production, depending on the experiment, over the most optimistic HCT-8 models. Oocyst identity was confirmed using a variety of microscopic- and molecular-based methods. This culturing system will accelerate research on Cryptosporidium and the development of anti- Cryptosporidium drugs.